Outcomes After Endoscopic Port Surgery for Spontaneous Intracerebral Hematomas - Ochalski, Pawel; Chivukula, Srinivas; Shin, Samuel; Prevedello, Daniel; Engh, Johnathan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Background Spontaneous intracerebral hemorrhages (ICHs) cause significant morbidity and mortality. Traditional open surgical management strategies offer limited benefit except for the most superficial hemorrhages in select patients. Recent reports suggest that endoscopic approaches may improve outcomes, particularly for deep subcortical hemorrhages. However, the management of these patients remains controversial. We reviewed our experience using endoscopic port surgery to identify characteristics that may predict acceptable outcomes.Materials and Methods We completed a retrospective chart and imaging review of patients who underwent endoscopic port surgery for evacuation of spontaneous ICH at a single center. Data were gathered regarding patient demographics, hemorrhage locations, operative findings, and clinical outcomes.Results From 2007 to 2011, 18 patients underwent evacuation of spontaneous intracerebral hematomas using an endoscopic port. The mean age in years was 62 years (range, 43–84 years). Six of 18 patients (33%) died before discharge, and 2 others (11%) died after at least 1 month of survival. Of 12 initial survivors, all were discharged to a rehabilitation or nursing facility. Complete hematoma evacuation was achieved in 7 of 18 patients, with the remaining 11 having a partial evacuation. The patients who died (n = 6) before discharge were statistically more likely to have a left-sided hemorrhage, partial evacuation, or older age than the survivors; death at least 1 month after evacuation was additionally associated with greater preoperative hematoma volumes.Conclusions Our series demonstrates that endoscopic port surgery for acute intracerebral hematoma evacuation has the ability to achieve significant decompression of large and deep-seated hematomas. Patient age, extent of evacuation, laterality, and preoperative hematoma volume appear to influence patient outcome. Most overall outcomes remain poor. Future studies are necessary to determine if surgical evacuation is in fact superior to best medical treatment and if so, to validate, refute, or further identify characteristics that define surgical candidates.
Keywords: endoscopic port surgery; hematoma; minimally invasive; outcomes; characteristics